PENYULUHAN BAHAN TAMBAHAN BERBAHAYA PADA JAMU DAN KOSMETIK DI PONDOK PESANTREN MADJID AMIN MALANG - Widiyana, Anita Puspa; Alhabsyi, Mochammad Alfian; Nabilah, Sayidati; Wardah (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
The harmful additives have the potential to cause health problems. Generally, herbal medicine and cosmetics circulating in the community are safe products. However, the increase in the distribution of herbal medicine has triggered the addition of harmful additives to improve the therapeutic effect. Cosmetics are used to clean, beautify, change the appearance, and/or improve body odor in good condition. The wide selection of cosmetics makes it highly attractive to the public. The socialization aimed to increase knowledge and awareness of harmful additives in medicinal herbs and cosmetics circulating in the community. Based on the results of observations, all students at Madjid Amin Islamic Boarding School are active students and can be said to have reached adulthood. Therefore, using herbal medicine and cosmetics that were popular with adults was not infrequent. The method of socializing through material presentations, practical training, and questionnaire administration before and after the event. The results of the socialization activities showed that the participants were very enthusiastic about the material and asked the speaker many questions. In addition, at the time of the practice of identification of harmful ingredients, participants were able to identify the ingredients of harmful ingredients in cosmetics or herbal medicine provided by the community service team. Activities of counseling on harmful additives in cosmetics and herbal medicine were declared successful in increasing knowledge in participants as measured by the results of questionnaires. Counseling activities were declared successful in increasing knowledge in students.